Phenology and Molecular Characterization of Annona Genotypes - Mahla, Jagruti S.; Soni, N. V.; Patel, Ashita; Patel, P. C.; Zala, H. N.; Dave, G. S. (International Journal of Bio-resource and Stress Management, 2024)
The experiment was conducted during July, 2020–January, 2021 at Agroforestry Research Station, Sardarkrushinagar Dantiwada Agricultural University, Sardarkrushinagar, Gujarat, India. Annona belongs to the family Annonaceae. The Annonaceae fruits are morphologically uniform but each type has a unique taste, flavour pulp colour and texture. The study revealed three types of leaf shapes (ovate, elliptic and lanceolate), leaf apex (acute, rounded and obtuse), leaf base (acute, rounded and acuminate), fruit shape (cordate, rounded and irregular), medium and late time of harvest maturity, overlapping and smooth segmentation of the surface and only one type for fruit at peduncle end i.e., inflated. The biochemical analysis of Annona species revealed the ranges of TSS (18.39 to 28.32 °B), TA of pulp (0.18–0.80%), reducing sugar (15.02–19.44%), non-reducing sugar (2.77–5.92%), total sugar (17.79–23.70%), ascorbic acid (27.55–43.10 mg 100 g-1) and phenol (0.18–0.36%). The DNA was amplified using fourteen simple sequence repeats primers and twenty-six alleles were found with an average of 1.86 alleles loci-1. The polymorphism information content value of the SSR markers was in the range of 0.09 to 0.38. A dendrogram was developed based on the cluster analysis, which revealed similarity index values varied from 0.58 to 1.00 with an average of 0.83. Based on the dendrogram the genotypes were clustered into two main clusters viz., A and B. Cluster A has sixteen genotypes and cluster B has two genotypes belonging to different Annona species. These results concluded that SSR markers could be efficiently used to study divergence among Annona genotypes.